From Intelligence Superiority to Decision-Making Superiority: Lessons from the Strait of Hormuz for the Strategic Security of the Strait of Malacca - Joshua Insetyadi B; Muhammad Halkis; Agus Hasan Sulistiyono Reksoprodjo (International Journal of Education, Management, and Technology, 2026)
Although maritime chokepoints have received substantial attention in research on maritime security, energy security, and military power, limited scholarship has examined how multi-domain intelligence is converted into decision superiority and applied across distinct chokepoint environments. This study investigated the intelligence-to-decision mechanisms demonstrated in the Strait of Hormuz and assessed their conditional relevance to the strategic security of the Strait of Malacca. It employed a qualitative, theory-guided case study design integrating process tracing, structured, focused comparison, and source triangulation. The analysis covered the period from 2019 to August 2026, treating the Strait of Hormuz as the primary critical case and the Strait of Malacca as the application case. Data were drawn from peer-reviewed literature, official documents, international organizations, reputable news agencies, strategic and defense research institutions, and open-source intelligence. The findings reveal that maritime strategic effects emerge through an interconnected sequence comprising multi-domain intelligence, surveillance, and reconnaissance (ISR), intelligence fusion, decision superiority, operational conversion, and strategic effects. Intelligence superiority alone does not guarantee strategic success; its effectiveness depends on converting integrated intelligence into timely, accurate, coordinated, and contextually appropriate decisions. The study contributes to maritime security scholarship by conceptualizing decision superiority as the mechanism linking intelligence architecture to strategic effects and demonstrating that lessons from the Strait of Hormuz should be transferred as adaptable mechanisms rather than replicated as military doctrines. For Indonesia, securing the Strait of Malacca requires prioritizing persistent ISR, multi-sensor intelligence fusion, interorganizational interoperability, rapid decision-making, and resilient surveillance instead of unilateral sea-denial strategies. These findings advance an intelligence-centric approach to maritime security and provide practical guidance for strengthening Indonesia’s maritime intelligence architecture while preserving freedom of navigation and regional cooperation. Further research should test the proposed intelligence-to-decision mechanism using additional primary sources and comparative evidence from other strategic maritime chokepoints.